Hirayama Disease: A Case of an Albanian Woman Clinically Stabilized Without Surgery - Antonioni, Annibale; Fonderico, Mattia; Granieri, Enrico (Frontiers in Neurology, 2020)
Hirayama Disease (HD) is a rare clinical condition that usually affects young people and with preference for Asian males. It appears with unilateral distal amyotrophy, or asymmetric bilateral, of an upper limb which is to refer to an involvement of the spinal metamers C7-C8-T1. A clinical case of a female patient of Albanian nationality is described, with onset of the disease in adulthood and clinical and electrophysiological features suggestive of HD, without any characteristic imaging findings. Clinical investigations, EMG and radiological data facilitated the diagnosis and allowed the exclusion of degenerative forms of the motor neuron and radiculopathies.